Digital Teaching Reinvented: The Effectiveness of AI-Based and IFP-Based Interactive Media in Improving Teacher Competence - Brezto Asagi Dewantara; Eka Cahya Sari Putra; Fitri Nurmahmudah (Institut Agama Islam Negeri Palopo, 2025)
Digital transformation in education requires teachers to have competencies that are not only technically strong, but also adaptive and creative in utilizing smart technologies. This study aims to analyze the effectiveness of